Pemanfaatan Limbah Cair Tahu dan Nutrisi AB Mix sebagai Nutrisi oleh Tanaman Mentimun (Cucumis sativa L.) secara Hidroponik - Zary, Rizky Qurnia; Islan, Islan; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research was intended to find out the effect of interaction between AB mix nutrition and tofu liquid waste in order to get the best AB mix concentration and tofu liquid waste concentration for the plant growth and cucumber plant yield (Cucumis sativa L.) hidroponically. This research took place in the Green House of Faculty of Agriculture University of Riau during July to November 2017. This research was conducted experimentally by using complete randomized factorial design (RAL) which have two factors and three replication. Factor 1 the concentration of AB mix nutrition (K), where: K1 = 0 ml, K2 = 2 ml.l-1,K3 = 4 ml.l-1 and Factor 2 the concentration of tofu liquid waste (L) with: L1 = 20%, L2 = 40%, L3 = 60%, L4 = 80%. The result showed that, the interaction of AB mix concentration and tofu liquid waste indicated non significant effect on all parameters. The single factor of AB mix indicated non significantÂ effect on the length and the diameter of fruits but had significant effect on other parameters. In a single factor tofu liquid waste indicated a significant effect only on the length of fruits. Therefore, the application of 4 ml.l-1 of AB mix concentration and 60% concentration of tofu liquid waste indicated the best result of plant growth and the production of the cucumber.Keywords: AB mix nutrition, tofu liquid waste, cucumber, hydroponic